Associated factors of delirium tremens in the inpatients receiving psychiatric consultation-liaison service for alcohol-related problems - Kalayasiri, Rasmon; Sareedenchai, Pairoj (Chulalongkorn Medical Journal, 2022)
Background: Alcohol withdrawal delirium or delirium tremens (DTs) is found variably between 3.0 - 48.5% in different settings. Objective: The study aims to investigate the prevalence of DTs in the inpatients of a university hospital who had alcohol use problems and were sent to receive psychiatric consultation-liaison service and to identify related factors for DTs in this cohort. Methods: Demographics, alcohol use variables, and blood chemistry were obtained from fifty-three inpatients with alcohol problems that were sent to receive psychiatric consultation-liaison service at the Department of Psychiatry, King Chulalongkorn Memorial Hospital, Thailand. The severity of alcohol withdrawals and delirium were measured by using the Clinical Institute Withdrawal Scale for Alcohol-revised (CIWA-Ar) and the Delirium Rating Scale-Revised 98 (DRS-R-98), respectively. Results: Of the 53 inpatients, 50 (94.3%) were male (mean age 45 years) and 31 (58.5%) had DTs. Patients with DTs were more likely to have a trend toward drinking the higher amount of maximum alcohol consumption per day (> 30 standard drinking units) and drinking liquor than the non-DTs group. Level of bicarbonate, creatinine, aspartate transaminase were associated with DTs at admission (P < 0.05). Abnormal alkaline phosphatase level was associated and nearly associated with severity of delirium and alcohol withdrawal symptoms respectively. Logistic regression analysis showed that bicarbonate and creatinine were risk factors for DTs. Conclusion: Prevalence of DTs is high in the inpatients receiving psychiatric consultation-liaison service for alcohol-related problems. Blood chemistry, especially those involved with kidney and liver function at the time of admission, may be used to predict the occurrence and severity of DTs.